The Investigating EFL Students’ Anxiety during Classroom English Presentation: A Mixed-methods Study - Windy; Tri Wintolo Apoko (STAIN Sultan Abdurrahman Kepulauan Riau, 2025)
Classroom presentation is an essential aspect of EFL students' speaking skills, as it involves actively conveying and expressing ideas in front of an audience. However, this activity often causes anxiety that can hinder students' performance. Therefore, this study aims to investigate the various factors that might contribute to the anxiety experienced by EFL students during classroom presentations, as well as identify coping strategies that can help them address their anxiety and enhance their speaking skills. In this study, mixed methods were used by combining quantitative and qualitative approaches to obtain a more in-depth understanding of students' anxiety and the efforts that can be carried out to reduce its impact on speaking performance. The results showed that most students experienced medium level of learning anxiety, while their speaking ability was quite good. However, the relationship between anxiety and presentation skills in English did not show a strong enough correlation. Qualitatively, anxiety affects cognitive impairment, fluency and cohesiveness in speaking, as well as students' confidence level. In addition, the results of this study also highlighted some effective strategies that can be implemented to effectively manage anxiety, such as applying breathing techniques, practicing regularly, and speaking at a slow tempo. Therefore, students are advised to make a more thorough preparation before making an English presentation in class to increase their confidence and speaking fluency.